An Integrated Approach to Bias in a Longitudinal Survey in the United Kingdom: Assessing Construct, Method, and Item Bias in the General Health Questionnaire (GHQ-12). (October 2019) - Benítez, Isabel; Adams, Byron G.; He, Jia
Construct, method, and item bias are three levels of measurement bias (i.e., internal bias) essential for valid group comparisons. While many studies often focus on only one level of bias, an integrated perspective on bias is still missing, especially in longitudinal designs. The aim of this study is to address bias in an integrated manner, using four waves of data in the U.K. Longitudinal Household Panel Survey. Responses to the General Health Questionnaire (GHQ-12) from natives and two generations of immigrants were used to analyze the three levels of bias. While the basic structure of the GHQ-12 was stable across groups and time, item and method bias decreased with repeated administrations. Results were confirmed with a sensitivity test. The integrated results allowed for a distinction between temporal sources of bias that became smaller over time and sources affecting valid comparisons persistently. We discuss the implications for mental health assessment.